As atividades do psicólogo no complexo penitenciário de Pedrinhas: Uma análise a partir da ergologia da atividade - SOARES, Adivan Jarbas Moreira (2018)
After The United States of America and China, respectively, Brazil is the 3rd country in the ranking for absolute number of inmates in the world. There are, approximately, 800 thousand detainees in the country. There are no signs of changing this perspective, once the national prison population keeps increasing about 7% a year, following public policies designed with punitive tone. In order to handle the demand, a number of professionais of different areas is required, therefore increasing the need for researches with the purpose of enhancing the effectiveness of the labour done. Hence, the focus of this paper is the developmente of the psichologist’s activities inside prison facilities, more especifically, following the work of psychologists at Pedrinhas correctional facility. Pedrinhas prison is composed of 6 independent units, and has more than 2.300 inmates. Most part of these prisoners are from the state of Maranhão. In such facilities, psychologists have worked, for decades. Their work is, historically, made of expert reports and evaluation, for diagnosis and prognosis. However, the community of psychologists have queried the use and abuse of disciplinarian techniques, and have researched for new alternatives for psychological intervetion in the prison system. Thus, this research main scope is to analyze the activities developed by psychologists at Pedrinhas prison facility from the Ergology Activity perspective. In order to accomplish that, this present paper has, as specific objectives: a) To identify the former norms that guide the work done by the psychologists at Pedrinhas correctional facility, seeking to understand further the precedents of the current situation at this correctional center; b) To analyze the procedures performed by Pedrinhas’ psychologists; and c) To identify, using Ergology, the perspectives and values present in the psychologists’ speech during the performance of their activities. Ergology is a process of grasping and analyzing human activity, which comprises several subjects and areas of knowledge, the latter arisen from laborers experiences, to analyze labour situations. This analysis is made from the laborer’s perspective, and has the objective of investigate the permanent debate of norms and values that renew, indefinitely, human activity.